1975
DOI: 10.1016/s0006-3495(75)85854-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipid, not polarized water, is responsible for the semipermeable properties of living cells

Abstract: It has recently been proposed that the semipermeable surface barrier of living cells is in fact provided by water polarized in multilayers by the cellular protein, and not by the lipids of the cell membrane as had been widely supposed. This review paper summarizes a large and diverse body of recent experimental work, concerned with the structure and function of biological membranes in general and with the passive permeability properties of cell surface membranes in particular, which does not support the polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The working equations relating the complex capacitance CM, Cm = C' -ic, (1) of the membrane system to the experimentally (Am, 4m) are (cf Appendix) observable data CI = C Am cos (km -_ ) (2) and C" = C0 A sin (Om -o0),…”
Section: Bilayer Thickness Determinationsmentioning
confidence: 99%
“…The working equations relating the complex capacitance CM, Cm = C' -ic, (1) of the membrane system to the experimentally (Am, 4m) are (cf Appendix) observable data CI = C Am cos (km -_ ) (2) and C" = C0 A sin (Om -o0),…”
Section: Bilayer Thickness Determinationsmentioning
confidence: 99%
“…However, their function in the membranes of prokaryotic cells is not clear. Several investigators have reported that glycolipids in the membranes of A. laidlawii are mono-and di-glycosyldiacylglycerol (Bhakoo et al, 1987 ;Dahlqvist et al, 1995 ;Gross & Rottem, 1979 ;Shaw 1968) and that they might play an important role in physiological functions such as membrane viscosity (De Kruyft et al, 1973 ;McElhaney et al, 1970 ;McElhaney, 1975 ;Rottem et al, 1973). Several reports suggest that the fusion of mycoplasmas with eukaryotic cells may result in the delivery of mycoplasma components into the host cells (Toole & Lowdell, 1990 ;Franzoso et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Ling (1973) holds the view that the water polarized in the multilayers by the cellular proteins and not the membrane lipid provides the living cells with their semipermeable surface barrier. On the other hand, McElhaney (1975) holds the view that the membrane lipid and not the polarized water is responsible for the semipermeable properties of living cells. The present investigation on electrical conductance of lipid membranes with and without proteins is of relevance in the context of this controversy.…”
Section: Electrical Conductance Characteristics Of Some Human Erythro...mentioning
confidence: 99%